RESPON EKSPLAN DAUN TANAMAN JERUK MANIS (Citrus sinensis L.) SECARA IN VITRO AKIBAT PEMBERIAN NAA DAN BA - Sri Wulandari; Wan Syafii; Yossilia ' (Program Studi Pendidikan Biologi, 2004)
The effect of Naphthalene Acetic Acid (NAA) and Benzyl Adenine (BA) of concentration of leaf eksplan Citrus sinensis L. by in vitro was studied at tissue culture laboratory of Balai Benih Induk Pekanbaru, The experiment was conducted using Completely Randomized Design (RAL) with three replicates. The treatment consist of A (without NAA and BA), B (0,1 ppm NAA and 0,1 ppm BA), C (1 ppm NAA and 0,1 ppm BA), D (10 ppm NA and 0,1 ppm BA), E (0,1 ppm NAA and 1 ppm BA). F (1 ppm NAA and 1 ppm BA). G (10 ppm NAA and 1 ppm BA), H (0,1 ppm NAA and 10 ppm BA), I (1 ppm NAA and 10 ppm BA) and J (10 ppm NAA and 10 ppm BA),The results of this experiment showed that respond growth of good leaf eksplan. NAA and BA at concentration 0,1; 1 and 10 ppm can yield forming o f root and callus can’t forming of buds. Callus initiation and root quickest of concentration 10 ppm NAA and 0,1 ; 1; 10 BA ppm that is 10,00 and 14,66. Amount root o f concentration 1 ppm NAA and 10 ppm BA is 29,66 and wet weight of callus high at gave of concentration 10 ppm NA and 10 ppm BA is 0,25 gr. Key words : Citrus Sinensis L, BA, Eksplan, NAA